2018
DOI: 10.1080/19390211.2018.1472708
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Sodium Phosphate Supplementation on Physiological Responses to Submaximal Exercise and 20 km Cycling Time-Trial Performance

Abstract: The aim of this study was to examine the effects of sodium phosphate (SP) supplementation on physiological responses to submaximal exercise and 20 km cycling time-trial performance. Using a randomized, double-blind, crossover design, 20 endurance-trained male cyclists (age: 31 ± 6 years; height: 1.82 ± 0.07 m; body mass: 76.3 ± 7.0 kg; maximal oxygen uptake [V̇O]: 57.9 ± 5.5 mL·kg·min) completed two supplementation trials separated by a 14-day washout period. The trials consisted of 10 minutes of cycling at 65… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…In our study, we did not observe any significant changes in VO 2 and RER during exercise at a given workload. Similarly, no significant decrease in submaximal RER or VO 2 after phosphate loading was reported in studies conducted under normoxic conditions [10,38,44,69]. Our findings suggest that phosphate salts did not shift the use of metabolic substrates towards fat utilization and did not reduce the energy cost of exercise at an intensity > 60% of VO 2max in hypoxic conditions.…”
Section: Discussionsupporting
confidence: 48%
“…In our study, we did not observe any significant changes in VO 2 and RER during exercise at a given workload. Similarly, no significant decrease in submaximal RER or VO 2 after phosphate loading was reported in studies conducted under normoxic conditions [10,38,44,69]. Our findings suggest that phosphate salts did not shift the use of metabolic substrates towards fat utilization and did not reduce the energy cost of exercise at an intensity > 60% of VO 2max in hypoxic conditions.…”
Section: Discussionsupporting
confidence: 48%
“…These findings are not isolated, with several other studies reporting no ergogenic effect of sodium phosphate on time-trial performance or average power (e.g. Buck et al 2014;Brown and Glastier, 2019;Brewer et al 2014). In fact, at doses of 25 mg/kg/day, Buck et al (2014) suggested the effects may even be deleterious.…”
Section: Discussionmentioning
confidence: 80%
“…Studies conducted under normoxic conditions have found that phosphate salt supplementation leads to a 3-12% increase in VO 2max and an improvement in aerobic exercise performance [20][21][22][23][24][25]. However, not all research supports these beneficial phosphate loading effects [26][27][28][29] and recommendations for the use of phosphates by athletes remain ambiguous [19,30,31]. Research into the effects of phosphate salts under hypoxic conditions is scarce.…”
Section: Introductionmentioning
confidence: 99%